The impact of increasing saline flush volume to reduce the amount of residual air in the delivery system of aortic prostheses—a randomized controlled trial - Szentiványi, András; Borzsák, Sarolta; Vecsey-Nagy, Milán; Süvegh, András; Hüttl, Artúr; Fontanini, Daniele Mariastefano; Szeberin, Zoltán; Csobay-Novák, Csaba (Frontiers in Cardiovascular Medicine, 2024)
Background Air embolism is a known risk during thoracic endovascular aortic repair (TEVAR) and is associated with an incomplete deairing of the delivery system despite the saline lavage recommended by the instructions for use (IFU). As the delivery systems are identical and residual air remains frequently in the abdominal aortic aneurysm sac, endovascular aortic repair (EVAR) can be used to examine the effectiveness of deairing maneuvers. We aimed to evaluate whether increasing the flush volume can result in a more complete deairing. Methods Patients undergoing EVAR were randomly assigned according to flushing volume (Group A, 1× IFU; Group B, 4× IFU). The Terumo Aortic Anaconda and Treo and Cook Zenith Alpha Abdominal stent grafts were randomly implanted in equal distribution (10-10-10). The quantity of air trapped in the aneurysm sac was measured using a pre-discharge computed tomography angiography (CTA). Thirty patients were enrolled and equally distributed between the two groups, with no differences observed in any demographic or anatomical factors. Results The presence of air was less frequent in Group A compared to that in Group B [7 (47%) vs. 13 (87%), p = .02], and the air volume was less in Group A compared to that in Group B (103.5 ± 210.4 vs. 175.5 ± 175.0 mm3, p = .04). Additionally, the volume of trapped air was higher with the Anaconda graft type (p = .025). Discussion These findings suggest that increased flushing volume is associated with a higher amount of trapped air; thus, following the IFU might be associated with a reduced risk of air embolization. Furthermore, significant differences were identified between devices in terms of the amount of trapped air. Clinical trial registration [NCT04909190], [ClinicalTrials.gov].